Workplace envy through the lens of leader–member exchange: evidence from higher educational institutions - Sunali Bindra; Bhumika Achhnani; Netra Neelam (Cogent Business & Management)
With the focus on organizations to emotionally engage employees at the workplace, the research intends to illustrate the importance of negative emotions like workplace envy (WPE) and positive emotions like perceived organizational support (POS) toward outcomes like job satisfaction (JS) and intention to quit (IQ). The paper seeks to determine how perceived organizational support is essential to job satisfaction and obstructs the intention to quit. Within the higher education sector’s top and middle management levels, 708 individuals were surveyed. The partial least squares (PLS) method was utilized, and the SMART-PLS 3.0 software tool was used to investigate the potential causal connections between the constructs. The mediating role of workplace envy and the role of perceived organizational support as a moderator of job satisfaction and intention to quit induced by Leader-member exchange (LMX) is analyzed. These variables collectively impact the quality of relationships within the workplace. Thus, managing these factors can assist organizations in achieving a more conducive, satisfying, and active workforce. It is the first study of its kind within the Indian higher education sector. It tries to figure out what role workplace envy and perceived organizational support play in explaining how LMX affects job satisfaction and intention to quit.